Protectors of Privacy : Regulating Personal Data in the Global Economy - Newman, Abraham, 1973- (Book collections on Project MUSE., 2008)
"From credit-card purchases to electronic fingerprints, the amount of personal data available to government and business is growing exponentially. All industrial societies face the problem of how to regulate this vast world of information, but their governments have chosen distinctly different solutions. In Protectors of Privacy, Abraham L. Newman details how and why, in contrast to the United States, the nations of the European Union adopted comprehensive data privacy for both the public and the private sectors, enforceable by independent regulatory agencies known as data privacy authorities. Despite U.S. prominence in data technology, Newman shows, the strict privacy rules of the European Union have been adopted far more broadly across the globe than the self-regulatory approach championed by the United States. This rift has led to a series of trade and security disputes between the United States and the European Union."--Jacket